2015
DOI: 10.1016/j.rbmo.2015.09.010
|View full text |Cite
|
Sign up to set email alerts
|

The place of reconstructive tubal surgery in the era of assisted reproductive techniques

Abstract: Assisted reproductive techniques yield high rates of success for women with tubal factor infertility. Because they are potentially effective for all categories of infertility, for two decades, clinical and basic research in infertility has been focused on IVF techniques and outcomes, rather than developing surgical techniques or training infertility subspecialists in tubal microsurgery. Nonetheless, in comparison with IVF, reconstructive tubal surgery is inexpensive and offers multiple opportunities to attempt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Experience with laparoscopy and microsurgery, as early as the mid-1980s, demonstrated that many complex fertility-enhancing procedures can be performed by means of minilaparotomy with a microsurgical approach (57, 58). In addition, use of special measures allowed many these procedures to be performed as day surgery, and for the patients to have a postoperative course not dissimilar from those who had a laparoscopic surgery (59,60). In the absence of comparative evidence and reported successful experience, it may be advisable to approach suitable cases with the use of minilaparotomy, minilaparotomy assisted by laparoscopy, or vice versa.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Experience with laparoscopy and microsurgery, as early as the mid-1980s, demonstrated that many complex fertility-enhancing procedures can be performed by means of minilaparotomy with a microsurgical approach (57, 58). In addition, use of special measures allowed many these procedures to be performed as day surgery, and for the patients to have a postoperative course not dissimilar from those who had a laparoscopic surgery (59,60). In the absence of comparative evidence and reported successful experience, it may be advisable to approach suitable cases with the use of minilaparotomy, minilaparotomy assisted by laparoscopy, or vice versa.…”
Section: Figurementioning
confidence: 99%
“…Despite our significant progress in gynecology in general and reproductive surgery, in particular, in concert with the improvements in ART outcomes, we have experienced a significant decline in the use and teaching of reconstructive surgery. In vitro fertilization began increasingly to be offered as the primary treatment option in cases of tubal and peritoneal factor infertility (60). Surprisingly, this change occurred despite the acceptance of laparoscopic access to perform many reconstructive tubal operations and the use of access by minilaparotomy for more complex procedures, both of which have become day procedures.…”
Section: Figurementioning
confidence: 99%
“…7 Honoré et al 8 in a meta-analysis examined the value of tubal microsurgery and macrosurgery, and hysteroscopic management of proximal tubal occlusion. They found that the average pregnancy rate was higher in women managed by hysteroscopic tubal recanalization compared with those managed with tubal microsurgery and open surgery or selective salpingography (48.9% vs. 38% vs. 28.8%, respectively).…”
Section: Tubal Cannulation and Artmentioning
confidence: 99%
“…This represents a live birth rate of 32.4% among the patients followed, and a rate of 25.6% if we include all lost to follow-up as failures. Based on the American Fertility Society classification, 73 of these cases had severe tubal damage and 13 (17.8%) of these had live births, whereas in the 17 whose damage was classified as mild, 10 (58.8%) had one or more births (3,4).…”
Section: Distal Tubal Diseasementioning
confidence: 99%
“…Therefore, the outcome depends on the degree of rigor in the microsurgical technique and in patient selection criteria. With a precise microsurgical technique, the tubal pregnancy rate is low, 2% (3,4).…”
Section: Tubal Anastomosis For Reversal Of Sterilizationmentioning
confidence: 99%